Conservative Islam Turn or Popular Islam? an Analysis of the Film Ayat-ayat Cinta - Lukman Hakim (Al-Jami'ah: Journal of Islamic Studies, 2010)
This paper offers a film and cultural studies analysis of the Indonesian religious film Ayat-ayat Cinta. It examines the way in which the film represents Islam in the context of the globalisation of the media industry, the wider cultural transformation and religious context in Indonesia. This paper argues that the film Ayat-ayat Cinta represents “popular Islam”, which resulted from the interaction between the santri religious variants and the film industry, capitalism, market forces and popular culture in Indonesia. Santri religious variants in this film are rooted in traditionalist, fundamentalist, modernist, and liberal Islam in Indonesia, and those Islamic groups which have undergone a process of conformity with capitalism and popular culture. As a result, the representation of Islam in this film is pluralist, tolerant, and fashionable.